2008
DOI: 10.1158/1535-7163.mct-08-0526
|View full text |Cite
|
Sign up to set email alerts
|

EBP1, an ErbB3-binding protein, is decreased in prostate cancer and implicated in hormone resistance

Abstract: Aberrant activation of the androgen receptor (AR) by the ErbB2/ErbB3 heterodimer contributes to the development of hormone resistance in prostate cancer. EBP1, an ErbB3-binding protein, acts as an AR corepressor. As EBP1 is decreased in preclinical models of hormone-refractory prostate cancer, we studied the expression of EBP1 in human prostate cancer. We found that the expression of the EBP1 gene was significantly decreased in prostate cancer tissues compared with benign prostate at both mRNA and protein leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 42 publications
4
73
0
Order By: Relevance
“…These mechanisms include (a) gene amplification and increased expression of the AR protein (6); (b) selection of point mutations in the AR ligand binding that can result in activation by nonandrogenic ligands (7), or mutations in other regions, such as the amino terminus (8) or the DNA-binding domain that confer oncogenic properties to the AR (9); (c) expression of alternatively spliced variants of the AR that lack the ligand-binding domain and are constitutive active (10)(11)(12); the mRNA of two of the most abundant isoforms, AR-V1 and AR-V7, showed an average 20-fold higher expression in HRPC specimens (n = 25) when compared with hormone-naive prostate cancer (n = 82; P < 0.0001; ref. 11); (d) changes in the expression ratios between AR, coactivators, and corepressors (13)(14)(15); (e) changes in the expression of enzymes involved in steroidogenesis (16); and ( f ) changes in signal transduction pathways (epidermal growth factor, insulin-like growth factor, interleukin-6, Wnt signaling, Stat5a/b, Ras/Raf/mitogenactivated protein kinase, phosphatidylinositol 3-kinase/Akt, etc.) that promote post-translational modifications (e.g., phosphorylation) of the AR and potentiate its activity under androgen-depleted conditions (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms include (a) gene amplification and increased expression of the AR protein (6); (b) selection of point mutations in the AR ligand binding that can result in activation by nonandrogenic ligands (7), or mutations in other regions, such as the amino terminus (8) or the DNA-binding domain that confer oncogenic properties to the AR (9); (c) expression of alternatively spliced variants of the AR that lack the ligand-binding domain and are constitutive active (10)(11)(12); the mRNA of two of the most abundant isoforms, AR-V1 and AR-V7, showed an average 20-fold higher expression in HRPC specimens (n = 25) when compared with hormone-naive prostate cancer (n = 82; P < 0.0001; ref. 11); (d) changes in the expression ratios between AR, coactivators, and corepressors (13)(14)(15); (e) changes in the expression of enzymes involved in steroidogenesis (16); and ( f ) changes in signal transduction pathways (epidermal growth factor, insulin-like growth factor, interleukin-6, Wnt signaling, Stat5a/b, Ras/Raf/mitogenactivated protein kinase, phosphatidylinositol 3-kinase/Akt, etc.) that promote post-translational modifications (e.g., phosphorylation) of the AR and potentiate its activity under androgen-depleted conditions (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Ebp1 is an ErbB-3 membrane-proximal region binding protein and is also a member of the proliferation related PA2G4 family. The Ebp1 protein can inhibit growth and proliferation and induce differentiation in tumor cells originating from breast carcinoma and carcinoma of the prostate which are positive for ErbB-2/ErbB-3 expression (Lessor et al, 2000;Zhang et al, 2008), suggesting that Ebp1 is a downstream effector molecule in the ErbB-3 signaling pathway. In addition, Cui et al (2010) have found that the expression level of the Epb1 protein in carcinoma of the gastric cardia tissues was substantially lower than that in normal cardia tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of EBP1 is associated with higher tumor grade and metastasis in prostate cancer (Zhang et al, 2008b). However, another study indicated EBP1 expression increased with disease progression (Gannon et al, 2008).…”
Section: Prognosismentioning
confidence: 97%
“…Sumoylation is required for nuclear translocation (Oh et al, 2010). In primary normal epithelial cells, EBP1 is confined to the cytoplasm (Zhang et al, 2008b).…”
Section: Localisationmentioning
confidence: 99%